When Social and Economic Goals Meet: The Double Dividend of Improving Farmers' Health Capital in Uganda. Issue 9 (1st September 2016) - Montaud, Jean-Marc; Tankari, Mahamadou
Abstract: Focusing on the relationship between farmers' health and agricultural productivity, we explore the potential effects of improving the current health care fee policy in Uganda. Using a microsimulated general equilibrium model, we show that alternative health fee reduction strategies might increase the chances of achieving simultaneous growth, poverty reduction and improved access to health for households while maximising the public spending effectiveness. However, these results seem very sensitive to the potential disruptive effects on public facilities that such a policy might generate so they must be contextualised within a broader perspective on the health system's efficiency.